Investigation of S960QL type high strength steel and its welded joints applying absorbed specific fracture energy and notch opening displacement - Sas, Illés; Lukács, János (Design of Machines and Structures, 2022)
Classical techniques of fracture toughness evaluation, such as determination of the plain-strain fracture toughness, or the critical value of the crack-tip opening displacement are complex methods. The determination of the absorbed specific fracture energy and the notch opening displacement is basically simpler; notched cylindrical tensile specimens characterized by different notch radii can be applied. S960QL type high strength steel and its welded joints without and with preheating were examined; notch opening displacement and absorbed specific fracture energy values were determined. Conclusions belong to the effect of the preheating and the sensitivity of the high strength steel, as well as the reliability of the applied material characteristics were drawn.